Running behavior and symptoms of respiratory tract infection during the COVID-19 pandemic - Cloosterman, K. L. A.; van Middelkoop, M.; Krastman, P.; de Vos, R. J. (Journal of Science and Medicine in Sport, 2021)
Objectives: To explore changes in running behavior due to the Coronavirus Disease 2019 (COVID-19) pandemic, assess presence of symptoms suggestive for COVID-19 and identify whether there is an association between running behavior and COVID-19. Design: Prospective cohort study. Methods: For this study we used a cohort of runners participating in an ongoing randomized controlled trial on running injury prevention among recreational runners. At baseline, demographic and training variables were collected. Seven weeks after starting the lockdown, information on running behavior (interval training, training with partner and physical distancing during training) and running habits (training frequency, duration, distance and speed) were obtained. Furthermore, healthcare utilization and symptoms suggestive for COVID-19 were assessed. To determine the association between running and symptoms suggestive for COVID-19, univariate and multivariate logistic regression analyses were performed. Results: Of the 2586 included participants, 2427 (93.9%) participants continued running during lockdown with no significant changes in mean weekly training variables. A total of 253 participants (9.8%) experienced symptoms suggestive for COVID-19 and 10 participants tested positive for COVID-19. Two participants were admitted to hospital due to COVID-19 with both one day of admission. Running behavior and running habits were not associated with the onset of symptoms suggestive for COVID-19. Conclusions: The large majority of runners in the Netherlands did not change their running habits during lockdown. No association between running behavior or running habits and onset of symptoms suggestive for COVID-19 was identified. This implicates that running outdoor during lockdown does not negatively affect health of runners.